An Empirical Analysis of The Trilemma: Inflation, Interest Rate and Exchange Rate Dynamics in Singapore - Chow, Yong Jin; Chan, Tze-Haw (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. This study considers the correlation among the Consumer Price Index (CPI), the Singapore /US dollar exchange rate, and the Singapore overnight rate average from 2012 to 2023 in Singapore. This small and open economy effectively manages its monetary policy to maintain a healthy inflation rate but has experienced high inflation rates and slow economic growth, raising questions about the effectiveness of the floating exchange rate system adopted by the Monetary Authority of Singapore in recent years. This study employs unit root and cointegration tests, impulse response functions, and variance decomposition. According to the vector error correction model specification, the production function primarily facilitated short-term adjustments toward long-term equilibrium; however, these adjustments were gradual, and it took more than two years to respond to system shocks. Analyses of the impulse response functions and variance decomposition indicate that changes in the variables resulted in analogous behavior patterns, with notable effects that primarily differ in their response to shocks. The empirical evidence supports the view that inflation controls are more sensitive to interest rate adjustment in Singapore. The findings of the present research provide valuable insights and have numerous important implications for the macroeconomic evaluation of Singapore. The study acknowledges that economies are subject to unforeseen events like global crises or pandemics, which can impact exchange rates and inflation beyond the scope of policy measures, and these might not be fully captured in the study. Keywords: Consumer price index, singapore overnight rate average (sora), monetary authority of singapore, free economy, monetary policy, foreign exchange policy